113Mothers' Knowledge and Attitudes in the First 1,000 Days of Life (HPK) Regarding Stunting Prevention Behaviors - Diah Evawanna Anuhgera; Yohana Putri Apryanti; Lidia Lusinta (JURNAL KEPERAWATAN DAN FISIOTERAPI (JKF), 2026)
Stunting is a public health problem caused by chronic malnutrition, particularly during the first 1,000 days of life (HPK). Maternal factors such as knowledge, attitudes, and behavior play a crucial role in stunting prevention efforts through appropriate feeding practices and utilization of health services. This quantitative research design employed a descriptive correlational approach and cross-sectional methods. The study location was the Kasih Ibu Galang Clinic, Deli Serdang Regency. The sample consisted of mothers with children aged 6–24 months, with 51 respondents selected using a purposive sampling technique. Data collection was conducted using a questionnaire. The results showed that 39.21% of respondents had good knowledge, 76.47% had positive attitudes, and 70.58% demonstrated good stunting prevention behaviors. Statistical analysis revealed a strong and significant relationship between knowledge and behavior (r=0.862; p=0.001) and between attitudes and behavior (r=0.727; p=0.002). There is a significant relationship between knowledge and attitudes during the first 1000 days of life (HPK) and stunting prevention behaviors. Improved health education and ongoing support are essential to support optimal feeding practices and reduce stunting prevalence.